I, minstrel The days in the life of a Spanish medieval actor - Álvarez Barrientos, María Marcela (2018)
The present poem takes into account historical aspects that occurred during theSpanish Middle Ages, mainly the cultural evolution present in the arts and letters’field after the process of reconquest by the Catholic Monarchs, in order to showfrom a tour through history, an approach to the possible reality of the minstrels, inother words, identify what were the daily, social and economic conditions, whichthese theatrical artists had to face, as part of the lower social classes the medievalera of the Christian Spain.